Literature Review: Aplying Warm Compressed For Breast Engorgement - Hardisman; Ziadati Shoulhuna; Yulizawati; Rauza Sukma Rita; Henni Fitria (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Breast engorgement is a condition in which the breasts become overly filled with milk, causing swelling, hardness, and pain. The prevalence of breast engorgement Indonesia in 2021 was 37.12%, which was the highest in ASEAN. The condition can be alleviated through non-pharmacological methods, such as warm compresses, which have no side effects. The study aimed to determine the application of warm compresses in managing breast engorgement. This study used a literature review with a scoping review approach. The study was conducted from November 2024 to February 2025. Data were collected from various digital databases, including PubMed Central, ScienceDirect, DOAJ, SINTA, Google Scholar, and Portal Garuda published from 2020 to 2024. Thematic analysis was used to interpret the data. Relevant articles was selected based on inclusion and exclusion criteria, and processed using the PRISMA-ScR flow diagram. 12 articles were identified for analysis.12 articles were analized by thematic analysis. The application of warm compresses 5 between 30 minutes in 3 days significantly reduces breast engorgement. Warm compress therapy offers several benefits, including reducing breast pain and swelling, promoting vasodilation, enhancing milk production, facilitating smoother milk flow, stimulating the let-down reflex, and improving breast emptying.